EPIDEMIOLOGY OF PRIMARY HYPERPARATHYROIDISM - N.F. NIYAZOVA; S.B. TURSUNOVA (Avicenna Tajik State Medical University, 2024)
This paper reviews epidemiological data on primary hyperparathyroidism (PHPT). PHPT is an endocrine disease caused by a tumor or hyperplastic changes in the parathyroid glands (PTG); it leads to disturbances in calcium-phosphorus homeostasis and can cause organ dysfunction. The results of epidemiological studies in various countries indicate an "epidemic" of PHPT at the end of the 20th century. Currently, PHPT ranks as the third endocrine problem in the world. Its prevalence is about 0.86-1% in people under 50 and 2% in people over 50. It was found that PHPT occurs more often in people aged 40-60 years, with an increase in the frequency of its detection after 25 years of age, especially in women after menopause. The review emphasizes the importance of PHPT, which represents a severe medical and social problem. Regular screening and the introduction of modern diagnostic methods play a vital role in the timely detection and management of PHPT, which is of great importance for improving patients' quality of life and preventing severe complications. When compiling the literature review, we used the following databases: PubMed, Embase, Medline, ScienceDirect, Cochrane Library, eLibrary, and CyberLeninka. The literature search was carried out using the following keywords: "epidemiology of primary hyperparathyroidism", "prevalence", "incidence", "normocalcemic hyperparathyroidism", "parathyroid gland", and "parathyroid hormone". The search identified more than 1070 scientific papers, from which 48 studies were selected. These studies cover the epidemiological aspects (incidence and prevalence) of PHPT conducted in various countries. The selection was done without considering each study's specific period and volume of observations. The selection process focused on studies using automated blood calcium analyzers to evaluate the impact of regular screening on the effectiveness of detecting PHPT. Works presenting both global and regional data were also included in the analysis. Studies that did not meet the established selection criteria were excluded.